Examining the good lives model and antisocial behaviour - Loney, Danielle M. (Psychology, crime & law, 2018)
This study examined the utility of the Good Lives Model (GLM) (Ward, T., & Stewart, C. A. (2003). The treatment of sex offenders: Risk management and good lives. Professional Psychology: Research and Practice, 34(4), 353-360. doi:10.1037/0735-7028.34.4.353) in understanding offending behaviour in students. Two hypotheses were made, consistent with the assumptions of the GLM. First, that participants would endorse the importance of the primary goods set out in the GLM. Second, that reports of antisocial behaviour would relate to a lack of effective strategies, or use of maladaptive strategies, to achieve primary goods. Participants (n = 340, M age = 20 years) completed a questionnaire (Measure of Life Priorities) assessing their pursuit, valuation, and achievement of the primary human goods as set out in the GLM and a Self-Report of Offending questionnaire. Results supported our hypotheses, and subsequently the assumptions of the GLM. Our findings support the continued use of the GLM as a theoretical and treatment oriented framework in diverse groups engaged in offending behaviour. Future research should continue to ground the GLM in empirical support.